(untitled) (Isagoge - Journal of Humanities and Social Sciences, 2025)
This study aims to examine the stage of public policy formulation in the context of Smart Cities. This stage, identified as the second stage of the Public Policy Cycle, stands out for its analysis of alternatives and definition of viable solutions to complex urban challenges. This process involves multiple stakeholders, fostering collaborative governance and citizen participation, which are established as fundamental elements of the Public Governance paradigm. Secondly, the concept of the Smart City is analyzed, including the six dimensions defined by Giffinger et al. (2007). Methodologically, we used a comprehensive literature review guided by the relevance of the references to the scientific field and also by the diversity of the authors, without ever neglecting the timeliness of the selected works. Finally, a limitation of the study is the scarcity of academic literature in Portugal that makes the connection between Smart Cities and Public Administration, underlining the need for further research in this field. We conclude that Smart Cities public policies, aligned with the Public Governance paradigm, are essential to exploit the potential of territories and meet the needs of the population, ensuring efficient and sustainable urban planning and improving citizens’ quality of life.